García Lorca: poetic text and language teaching - Campos, Alexandre Silveira (Universidade Estadual Paulista, 2020)
This paper has as its main purpose to discuss the various ways of using the poetry in the context of foreign language teaching practices. To this end, an activity will be presented that focuses on the literature and biography of the poet Federico García Lorca, directed to a class of Brazilian students of Spanish as a foreign language. From the idea that the mythical figure of the Grenadian poet attracts the student's attention and establishes the natural process of interest in the Spanish language and culture, some meaningful learning activity sequences can be developed. Thus, the student can build his own learning path, because at the same time that, through pedagogical activities, he reads, observes and analyzes the text (language) and the context (culture) of the poems, he has to - according to the intention of each activity - to be critically and ideologically positioned in the acquisition of a second language.